2020
DOI: 10.1111/jfb.14474
|View full text |Cite
|
Sign up to set email alerts
|

Arms as areas for larval development of migratory fish species in a Neotropical reservoir and the influence of rainfall over abundances

Abstract: The aim of the present study was to verify the use of the arms of the Itaipu Reservoir as areas of initial development for migratory fish species and to assess the relationship between rainfall and the spawning of migratory fish. Accordingly, fish larvae were collected from five arms of the reservoir from 2009 to 2016 using 0.5 mm plankton nets. Density was standardized as the number of larvae per 10 m 3 filtered water, and the captured larval and juvenile specimens were identified at the lowestpossible taxono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…Moreover, the presence of migratory species larvae in the mid and lower reaches does not necessarily indicate that spawning occurred in these locations, as various external stimuli are required to begin spawning, such as high flow velocity (Lopes et al., 2018). Instead, the spawning of migratory species is likely to have occurred in the remnant lotic areas of the tributaries, which maintain their preflooding flow characteristics, and followed by the drift of eggs and larvae to developmental areas in the arms (Sanches et al., 2020). These processes, therefore, result in a high level of overlap in the ordination of these reaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the presence of migratory species larvae in the mid and lower reaches does not necessarily indicate that spawning occurred in these locations, as various external stimuli are required to begin spawning, such as high flow velocity (Lopes et al., 2018). Instead, the spawning of migratory species is likely to have occurred in the remnant lotic areas of the tributaries, which maintain their preflooding flow characteristics, and followed by the drift of eggs and larvae to developmental areas in the arms (Sanches et al., 2020). These processes, therefore, result in a high level of overlap in the ordination of these reaches.…”
Section: Discussionmentioning
confidence: 99%
“…The longitudinal gradients are related to geomorphological, biological and chemical changes that occur along the main channel of the former river (river dam), whereas transversal (or lateral) gradients occur in the arms of the reservoir and are caused by changes in the former tributary beds (upstream and downstream of tributaries) (Oliveira et al., 2004; Thornton, 1990). Both gradients can be split into distinct fluvial, transitional and lacustrine zones (Sanches et al., 2020). Together, they constitute a spatial upstream‐downstream gradient showing differences in flow velocity, sedimentation rate, nutrient concentration and water transparency, which are influenced by hydrological seasonality and dam operation procedures (Baumgartner et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the two cycles, fish larvae in more advanced development stages (i.e., flexion and postflexion) had lower densities when compared to the other stages (e.g., yolk-sac larvae). As we used passive collection, we believe that larvae in flexion and post-flexion stages show some type of mobility (se also Sanches et al 2020), impeding them to drift with the river flux up to the ichthyoplankton net. Another possibility is that fish larvae in these more advanced stages are able to remain in areas less affected by the current (i.e., backwaters, including those close to vegetation), or in lateral lakes and ponds, which offer favorable conditions for feeding and survival.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies (e.g., Nunes et al 2015, Silva et al 2015, Marques et al 2018, Silva et al 2019, Sanches et al 2020) have shown or suggested the importance of tributaries for the maintenance of fish diversity in impounded areas. Therefore, the data presented here indicate that the Guareí River is important to the maintenance of fish assemblages in the Jurumirim Reservoir, given the connectivity between the two areas (i.e., free-flowing river and dam).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation